Characterisation of a Bacillus sp. Isolated from Soils Near Lake Maninjau Capable of Degrading Glyphosate - Rusnam, .; Rahman, Mohd Fadhil; Khayat, Mohd Ezuan; Nasution, Fachri Ibrahim; Umar, A.M.; Yakasai, Hafeez Muhammad (Journal of Environmental Microbiology and Toxicology, 2023)
Glyphosate and other soil toxins can be ecologically and financially sustainable bioremediation. When it pollutes the environment, the herbicide glyphosate—used extensively for weed control—poses serious dangers to animals and their ecosystems. A rice field that had been treated with glyphosate for several years was the subject of this investigation into the bioremediation capabilities of soil bacteria. We provisionally identified the most promising isolate as Bacillus sp. strain Unand1 using partial identification methods. Under ideal circumstances, this bacterium demonstrated considerable promise for degrading glyphosate. Bacterial experiments showed that the optimal conditions for glyphosate degradation were a pH of 6.0–7.0, a glyphosate concentration of 0.5–0.6 g/L, 30 °C, and a 1% (v/v) inoculum size. At 0.5 g/L glyphosate, the bacterium showed a two-day lag phase before degrading over 90% after six days of incubation. There was a remarkable 99% and 95% suppression rate of bacterial growth, respectively, when exposed to heavy metals such as Hg(II) and Ag(I). According to this study, this bacterium has bioremediation capability for glyphosate-contaminated settings. Full characterisation and optimization of this bioremediation approach require additional research, especially using molecular identification techniques. This method has the potential to greatly reduce the negative effects of glyphosate pollution on ecosystems and agricultural sustainability.